TPACK-Based Team Based Project Learning Design in Improving Digital Literacy Skills - Elok Fariha Sari; Fauji Koda; Imam Shofwan; Dewi Nilam Tyas (Journal of Nonformal Education, 2024)
Case method and team-based learning is one of the Key Performance Indicators (KPIs) implemented by the Ministry of Education and Culture of the Republic of Indonesia number 3/M/2021. Case method and team-based project learning is a learning that is charged to students to improve students' critical thinking skills, solve problems, find solutions, and foster communication skills. This learning is also useful for lecturers as teaching staff to improve higher abilities and skills. These learning methods need to be accompanied by an increase in digital literacy by students, whose application certainly cannot be separated from technology. Technology can make classroom learning more effective and efficient. To answer this challenge, the researcher is interested in developing a prototype of a TPACK-based team-based project learning module. This research has the following objectives: (1) Developing the design of a TPACK-based team-based project learning module in the form of a module prototype, (2) testing the feasibility of the module prototype, (3) testing the effectiveness of the module in improving students' digital literacy. The final result of this study is a prototype of a team-based learning design module that is feasible and effective so that it can be used as a guideline for the implementation of learning for the improvement of key performance indicators.